2020
DOI: 10.2139/ssrn.3706748
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does Societal Mobility Restriction Help Control the COVID-19 Pandemic? Evidence from Real-Time Evaluation

Abstract: Background Restrictions on mobility have been implemented by many countries to limit the spread of novel coronavirus infection (COVID-19) yet have important social and economic consequences. Their impact on reducing transmission is, however, inadequately understood. Methods We examined the association of COVID-19 incidence rates with mobility changes, defined as changes in categories of domestic location, against a pre-pandemic baseline, using country-specific daily incidence data on newly confirmed COVID-19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…By using real-time mobility data our work builds on this research and quantifies the policy strength in terms of how intensely people responded to the policy in practice, rather than the stringency of the policy as written. More recently, a pre-print by Oh et al examined the impact of societal mobility restrictions across 36 countries [ 12 ]. Oh and colleagues looked at “commuting mobility,” which is an aggregate variable of visits to different types of community locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using real-time mobility data our work builds on this research and quantifies the policy strength in terms of how intensely people responded to the policy in practice, rather than the stringency of the policy as written. More recently, a pre-print by Oh et al examined the impact of societal mobility restrictions across 36 countries [ 12 ]. Oh and colleagues looked at “commuting mobility,” which is an aggregate variable of visits to different types of community locations.…”
Section: Discussionmentioning
confidence: 99%
“…First, several European countries including Italy, Spain, and France were early hotspots of the COVID-19, hence more data is available to evaluate the first phase of the pandemic response [ 10 , 11 ]. Second, while earlier studies have assessed the impact of social distancing policies, understanding the mechanisms through which social distancing policies may work—such as by reducing overall aggregated population-level mobility—would provide critical validation of public health interventions [ 8 , 12 ]. Lastly, although not unique to Europe, understanding the relative effectiveness of mandatory vs. non-mandatory social distancing measures would enable public health officials across Europe and elsewhere to better implement early pandemic mitigation strategies in the future.…”
Section: Introductionmentioning
confidence: 99%
“…2) Restricting rides to certain users only, such as the buses and trams dedicated to vulnerable people, implemented in Iasi (Romania) and Auckland, New zealand, to provide transport services only to those who really need them [29][30]. 3) Shifting demand away from peak hours, as has been done with businesses in France and schools in the Netherlands, by encouraging people to spread out their journeys so that not everyone tries to travel at the same time during peak hours [31][32].…”
Section: Response Measures For Safeguarding Pt Use In Italy and Europementioning
confidence: 99%
“…Meanwhile, real-time mobility data helped elucidate the COVID-19 transmission and ascertain the implementation of strict control measures, which substantially mitigated the spread of COVID-19 [18][19][20] . Based on mobile phone location data, many studies found that reduced population mobility during the pandemic slowed down the spread of infections 21,22 . Public policies leading to decreased human mobility was associated with lower COVID-19 cases and deaths 23 and reduced COVID-19 spread 24 .…”
Section: Introductionmentioning
confidence: 99%